Can Human Capital Index Serve as A Blueprint for Economic Growth of The EU – Countries? - Katarína REMEŇOVÁ; Mária KMETY BARTEKOVÁ (Communications of International Proceedings, 2023)
Human Capital plays critical role in sustainable economic growth of each country. The Human Capital Index (HCI) combines demographic, education, and health dimensions on a complementary statistical and econometric basis. It is used by the World Bank in the area of human development for monitoring and comparison purposes, in time and space. The aim of the research article is to provide a more detailed look at the level of human capital from a country's macroeconomic perspective in relation to the country's income group and whether it is part of the EU or not. The basic methodology for measuring a country's human capital is the Human Capital Index. The data for the analysis of the Human Capital Index (HCI) were obtained from The World Bank Human Capital Project database. The results of non-parametric testing (Chi-Square Test of Independence) and rates of association between variables (using Cramér’s V) indicate that there is statistically significant difference between Income group of each country and EU – membership, as well as European region. The average value of the human capital index of the Eastern European countries (M = 0,66) lies at the level of Slovakia. Nevertheless, Slovakia lags behind the average HCI value of EU countries (HCI = 0.71) 5 points. In addition, the hypothesis about Membership in the EU and Income group of each country was confirmed. The result has shown when countries are part of the EU, their residents earn higher incomes, which placing them into the high-income group.
Keywords: human capital; human capital index; economic growth.